2022
DOI: 10.1002/2211-5463.13103
|View full text |Cite|
|
Sign up to set email alerts
|

Withdrawn: The LncRNA H19/microRNA‐29b‐3p/HMGB1 signaling axis contributes to the regulation of lung cancer cell growth

Abstract: The long non-coding RNA (lncRNA) H19 acts as a competitive endogenous RNA (ceRNA) of miR-29b-3p and has been reported to exert pro-tumorigenic roles in several cancer types.However, the role of lncRNA H19 in lung cancer is not fully understood. Here, we investigated the role of the lncRNA H19/microRNA-29b-3p (miR-29b-3p)/high mobility group box 1 (HMGB1) signaling pathway in lung cancer cell growth using 293T, NCI-H1975, Calu-3 and 2BS cell lines. Cell viability was determined using a cell counting kit-8 (CCK-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…6,[12][13][14] In addition, several miRNAs play an important role in cancer pathogenesis by regulating HMGB1 expression. [15][16][17] Bioinformatics analysis has revealed that miR-5683 and HMGB1 are abnormally expressed in GC tissue. Moreover, TargetScan database has predicted that HMGB1 is the target gene for miR-5683.…”
Section: Introductionmentioning
confidence: 99%
“…6,[12][13][14] In addition, several miRNAs play an important role in cancer pathogenesis by regulating HMGB1 expression. [15][16][17] Bioinformatics analysis has revealed that miR-5683 and HMGB1 are abnormally expressed in GC tissue. Moreover, TargetScan database has predicted that HMGB1 is the target gene for miR-5683.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-675, one of the targeted miRNAs of H19, is embedded in H19’s first exon, and H19 has been shown to inhibit the growth of the placenta before birth by regulating the processing of miR-675. H19 can also interact with other miRNAs, such as miR-326 ( Wei et al, 2019 ), miR-29a ( Cheng et al, 2019 ), miR-124-3p ( Liu et al, 2019 ), miR-152-3p ( Zheng et al, 2020 ), miR-22-3p ( Gan et al, 2019 ), miR-29b-3p ( Zhong et al, 2021 ), miR-193a-3p ( Ma et al, 2018 ), miR-612 ( Yu et al, 2020 ), to regulate biological processes in various types of cells by modulating the expression of downstream target factors, including twist family bHLH transcription factor 1 (TWIST1), thymine DNA glycosylase, integrin β3 (ITGB3), bromodomain containing protein 4 (BRD4), Snail1, high mobility group box 1 (HMGB1), presenilin-1 (PSEN1), and Bcl-2. Secondly, H19 is involved in regulating different processes in various types of cells by interacting with different proteins, such as methyl-CpG-binding domain protein 1 (MBD1) ( Monnier et al, 2013 ; Zhang et al, 2017 ), polypyrimidine tract-binding protein 1 (PTBP1) ( Liu et al, 2018 ), enhancer of zeste homolog 2 (EZH2) ( Luo et al, 2013 ), IGF2 mRNA-binding protein 1 (IGF2BP1) ( Runge et al, 2000 ), p53 ( Yang et al, 2012 ), K homology-type splicing regulatory protein (KSRP) ( Giovarelli et al, 2014 ), zinc finger E-box-binding homeobox 1 (ZEB1) ( Song et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%